Scenario Planning of IP-Based Financing Scheme Implementation Study on the Animation Creative Industry - Fitria Mahmudah; Mohammad Benny Alexandri; Yogi Suprayogi Sugandi (Green Publisher Indonesia, 2024)
This research aims to conduct a strategic review for the future, describe the possibility of an IP-based financing scheme for the animation creative industry, and formulate alternative strategies to overcome the main problem of limited access to financing faced in developing IP-based businesses. The IP-based creative economy financing scheme in Government Regulation Number 24 of 2022 was a breakthrough and legal innovation in the creative economy sector. Providing access to financing credit from financial institutions for creative industries to develop their businesses, but its application has just been implemented. The SWOT approach and Delphi-based scenario planning were adopted to attempt the IP-Based Financing Scheme policy to become a concept that can be implemented in Indonesia and effectively anticipate problems in future policy implementation. Creating a scenario design matrix involves exploratory scenario planning, which begins with identifying two primary driving variables. The critical uncertainties that drive policy changes in future financing schemes for the creative animation industry were Government capacity and social factors. A 2 x 2 scenario matrix framework was built to describe possible future conditions and the implications of each condition so that strategic options are offered for the Government from each scenario implication.